Proses Produksi Trolley HFNC di PT Poly Jaya Medikal - Ilham Ramadhan; Kardiman Kardiman; Farradina Choria Suci (Jurnal Ilmiah Wahana Pendidikan, 2022)
The tool used this time is a respiratory therapy device in the form of a High Flow Nasal Cannula (HFNC). This tool has the working principle of flowing high levels of oxygen rapidly so that oxygen levels in the patient's blood increase. To adapt HFNC equipment to medical needs, HFNC Trolley production is designed to make it easier to move positions according to equipment layout needs. The writing of this article aims to overcome the limitations of respiratory therapy tools and medical equipment adjustments. The method used is the design and processing of HFNC Trolley production process calculation data. The calculation results obtained that the HFNC Trolley product cycle time = 105 minutes/unit, then the actual cycle time product was 5.14 units/day, to complete the HFNC Trolley P.O. 200 production units, 8.3 units/day, with a product cycle time of 65 minutes/unit. for 24 working days, then cycle time product defects with 1% defects in a total production of 200 units producing 4 units of HFNC Trolley/day.